The Effect of late sowing and fertilizer rate on Cauliflower (Brassica oleracea var.botrytis) growth parameters and disease prevalence in Tripura, north-east India - KUMAR, VIJAY; CHHETRI, ASHOK (The Indian Journal of Agricultural Sciences, 2025)
The present study was focused on the effect of late sowing and fertilizer doses on the disease’s occurrence and other growth parameters of cauliflower. Analysis of the results comes to the conclusion that least diseases was occurred in the treatment which are having farm yard manure and also produces the maximum curd yield. Standard dose of NPK and ½ NPK + ½ FYM also exhibit the good results in term of growth parameters and less infection of diseases. Recommendation of late sowing of cauliflower in Tripura can be given as per the results obtained from the present study. From the farmer's perspective, it is advisable to use ½ NPK and ½ FYM during cultivation, which will save costs and minimize environmental hazards.